"y(t)\\to Y(p)"
"y^{(4)}(t)\\to p^4Y(p)-p^3y(0)-p^2y'(0)-py''(0)-y^{(3)}(0)"
For our case:
"y^{(4)}(t)\\to p^4Y(p)-43p^3-104p^2-432p-1024"
Then:
"p^4Y(p)-43p^3-104p^2-432p-1024-256Y(p)=0"
"(p^4-256)Y(p)=43p^3+104p^2+432p+1024"
"Y(p)=\\frac{43p^3+104p^2+432p+1024}{(p^2+16)(p+4)(p-4)}"
"\\frac{A}{p+4}+\\frac{B}{p-4}+\\frac{Cp+D}{p^2+16}=\\frac{43p^3+104p^2+432p+1024}{(p^2+16)(p+4)(p-4)}"
"A(p-4)(p^2+16)+B(p+4)(p^2+16)+(Cp+D)(p+4)(p-4)="
"=43p^3+104p^2+432p+1024"
"A(p^3-4p^2+16p-64)+B(p^3+4p^2+16p+64)+Cp(p^2-16)+D(p^2-16)="
"=43p^3+104p^2+432p+1024"
"A+B+C=43"
"-4A+4B+D=104"
"16A+16B-16C=432\\implies A+B-C=27"
"-64A+64B-16D=1024\\implies -4A+4B-D=64"
"2C=16\\implies C=8"
"2D=40\\implies D=20"
"A+B=35"
"-4A+4B=84\\implies B-A=21"
"B=28,A=7"
Then:
"Y(p)=7\\cdot\\frac{1}{p+4}+28\\cdot\\frac{1}{p-4}+\\frac{8p+20}{p^2+16}"
"\\frac{1}{p+4}\\to e^{-4t}"
"\\frac{1}{p-4}\\to e^{4t}"
"\\frac{p}{p^2+16}\\to cos4t"
"\\frac{1}{p^2+16}\\to \\frac{1}{4}sin4t"
Answer:
"y(t)=7e^{-4t}+28e^{4t}+8cos4t+5sin4t"
Comments
Dear enaira, You are welcome. We are glad to be helpful. If you liked our service, please press a like-button beside the answer field. Thank you!
Thank you! The answer is correct. though the solution is a bit too long.
Leave a comment